Content and impact of articles published by school psychology faculty. Issue 7 (20th May 2019) - Hulac, David M.; Aspiranti, Kathleen; Jacobson, Madeline; Schneider, Maryia; Johnson, Natalie
Abstract: School Psychology faculty members are expected to publish articles in peer‐reviewed journals that impact the fields of education and psychology. Both the content and the impact of the articles school psychologists publish may change across time and differ from other disciplines. The current analysis sought to understand average article impact, content, and research focus, and to describe those articles that have the highest impact factor. All of the articles ( n  = 3670) published by school psychology faculty between January, 2010 and December, 2015 were collected and examined. Three reviewers were trained over 2 hr to read abstracts and to classify the content of those abstracts. The literature was systematically classified into four categories: assessment, consultation, intervention, and professional issues. The title, keywords, and abstract were used to find the category of best fit for each publication. The majority of articles published fall into the broad category of Professional Issues. The average article is cited 17.68 times in Google Scholar and 4.9 times in Web of Science. These data will be useful to understand publication content trends and identify gaps in research.